Pengaruh Periklanan, Sales Promotion, Personal Selling Dan Publicity Terhadap Keputusan Pembelian Produk Aksesoris Mobil ( Studi Kasus Kilat Service Medan ) - Silvia Sofyan (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2017)
This research is aimed to analyze the influence of Advertising, Sales Promotion, Personal selling, and Publicity on Purchase Decision of Automotive Accesories at Kilat Service Medan. This is an associative type of research using a judgment sampling approach and the multiple linear regressions as the tools of analysis. 100 respondents were used as samples, with the hypothesis testing of F and t-tests, where data were analyzed using SPSS 21.0. The findings show that Advertising and Personal Selling do not have significant effect on Purchase Decision, while Sales Promotion, Publicity, and Word-of-mouth have significant influence on Purchase Decision.